2015
DOI: 10.1155/2015/846138
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Development of Semisolid Metal Joining Processing

Abstract: The semisolid metal joining (SSMJ) process or thixojoining process has recently been developed based on the principles of SSM processing, which is a technology that involves the formation of metal alloys between solidus and liquidus temperatures. Thixojoining has many potential benefits, which has encouraged researchers to carry out feasibility studies on various materials that could be utilized in this process and which could transform the production of metal components. This paper reviews the findings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Semisolid metal (SSM) forming is catching more and more theoretical and technical attentions because of its distinctive potential in near-net shaping [1]. In recent years, the light alloys have been studied extensively since its excellent characteristics have important effects on SSM processing [2][3][4][5][6][7][8][9]. Among them, as the most abundant metal on earth, aluminium alloys have the low-cost property, which are applied extensively to automobile and aerospace [2][3][4][5]8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semisolid metal (SSM) forming is catching more and more theoretical and technical attentions because of its distinctive potential in near-net shaping [1]. In recent years, the light alloys have been studied extensively since its excellent characteristics have important effects on SSM processing [2][3][4][5][6][7][8][9]. Among them, as the most abundant metal on earth, aluminium alloys have the low-cost property, which are applied extensively to automobile and aerospace [2][3][4][5]8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the light alloys have been studied extensively since its excellent characteristics have important effects on SSM processing [2][3][4][5][6][7][8][9]. Among them, as the most abundant metal on earth, aluminium alloys have the low-cost property, which are applied extensively to automobile and aerospace [2][3][4][5]8,9]. Thus, the study on the rheological behavior of AlSi4Mg2 alloy has significant meaning for the improvement and the development of SSM processing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an innovative route that can avoid the above mentioned problems inherent in fusion welding is required. Thixojoining is a possible technique that can weld the AISI D2 cold-work tool steel free from the above mentioned problems, as the process is carried at the semisolid state where the mechanisms of solidification and heat flow are different from other welding processes [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…During the last 30 years, several authors have shown that the thixojoining process has the potential to be used for a wide range of metal production processes. Notwithstanding some technical and technological differences between the available semi-solid joining processes, they can be classified into four categories: (1) joining metals by using semisolid slurries, (2) addition of functional features, (3) semisolid stir joining, and (4) semisolid diffusion joining [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation